An L-Shaped Incision for an Extensive Thoracic Aortic Aneurysm and Coronary Artery Bypass Using the Left Internal Thoracic Artery - Abe, Tomonobu; Suenaga, Hiroto; Oshima, Hideki; Araki, Yoshimori; Mutsuga, Masato; Fujimoto, Kazuro; Usui, Akihiko (AORTA, 2015)
An L-shaped incision combining an upper half mid-sternotomy and a left antero-lateral thoracotomy at the fourth intercostal space has been proposed by several authors for extensive aneurysms involving the aortic arch and the proximal thoracic descending aorta. This approach usually requires the division of the left internal thoracic artery at its mid position, thus making it unusable for coronary artery bypass. We herein report a modified surgical approach for simultaneous extensive arch and proximal thoracic descending aorta replacement and coronary artery bypass using the left internal thoracic artery combining a left antero-lateral thoracotomy at the sixth intercostal space and upper mid-sternotomy. The visualization of the whole diseased aorta down to the level below the hilum of the left lung was good, and the integrity of the left internal thoracic artery graft was preserved by early heparin administration before sternotomy.
Keywords: Thoracic Aortic Aneurysm; Coronary Artery Bypass; Mammary Arteries